Putin's energy agenda : the contradictions of Russia's resource wealth - Hedlund, Stefan, 1953- (Lynne Rienner Publishers, 2014)
The sudden arrival of massive energy wealth during Putin's long reign has turned Russia's focus to resources, with some good and some very bad results. Considering why the good-a windfall of money to pay debts and put the country's finances in order-has been so overshadowed by the bad-resource dependence, reliance on rents, and unbridled corruption-Stefan Hedlund explores the many dimensions of Russia's energy policies and politics.